Assessment, remediation, and post-remediation verification of mold in buildings - Hung, Ling-Ling; Marcham, Cheri; Miller, J. David; Springston, John P.; Weekes, Donald M. (AIHA, 2021)
For professionals conducting mold assessments in both residential and commercial buildings. The guideline discusses exposure and hazard assessments, determination of requirements to allow for the re-occupancy of a building, and post-remediation verification methodologies and techniques.